2019
DOI: 10.3389/fbioe.2019.00143
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Specification of Pluripotent Stem Cell Derived Endothelial Cells Toward Arterial and Venous Subtypes

Abstract: Endothelial cells (ECs) are required for a multitude of cardiovascular clinical applications, such as revascularization of ischemic tissues or endothelialization of tissue engineered grafts. Patient derived primary ECs are limited in number, have donor variabilities and their in vitro phenotypes and functions can deteriorate over time. This necessitates the exploration of alternative EC sources. Although there has been a recent surge in the use of pluripotent stem cell derived endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 103 publications
(140 reference statements)
0
14
0
Order By: Relevance
“…For many years, it was thought that blood flow was responsible for establishing vascular identity. The discovery that members of the Eph family are differentially expressed in arteries and veins from very early stages of development, prior to development of a functional circulation, was one of the first indications that artery‐vein identity is intrinsically programmed . Arterial and venous specification in the developing embryo can be genetically pre‐determined.…”
Section: Arterial and Venous Endothelial Cellsmentioning
confidence: 99%
“…For many years, it was thought that blood flow was responsible for establishing vascular identity. The discovery that members of the Eph family are differentially expressed in arteries and veins from very early stages of development, prior to development of a functional circulation, was one of the first indications that artery‐vein identity is intrinsically programmed . Arterial and venous specification in the developing embryo can be genetically pre‐determined.…”
Section: Arterial and Venous Endothelial Cellsmentioning
confidence: 99%
“…Further studies investigated whether EPCs differentiate into arterial or venous ECs in response to shear stress[ 3 ]. Obi et al [ 41 ] have demonstrated that controlled levels of shear stress in a flow-loading device increased the expression levels of the arterial EC markers ephrinB2, Notch1/3, Hey1/2, and activin receptor-like kinase 1, but decreased expression of the venous markers EphB4 and neuropilin 2.…”
Section: Shear Stress Promotes Endothelial Differentiation Of Stem Cellsmentioning
confidence: 99%
“…Most of the previous experimental systems involved the use of bioreactors or viscometers, like parallel plate flow and conical flow reactors[ 3 ]. To overcomes the limitations of macroperfusion systems in shear application throughput and precision, Toh and Voldman[ 54 ] used a multiplex microfluidic array that applied shear stresses varying by > 1000 times (1.6 × 10 -7 -1.6 × 10 -4 N/cm 2 ) to mouse ESCs.…”
Section: Shear Stress Promotes Endothelial Differentiation Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant differences in morphology between arterial and venous endothelium [ 182 , 183 ]. Arterial ECs are long and narrow or oval, while venous ECs are short and wide, which is related to the fact that the velocity of blood flow in the venous circulation is significantly lower than that in the arterial circulation.…”
Section: Heterogeneity Of Vascular Endotheliummentioning
confidence: 99%